Documenting the immune response in patients with COVID-19-induced acute respiratory distress syndrome - Lu, Junyu; Zeng, Xiaona; Lu, Weisheng; Feng, Jihua; Yang, Yegui; Wei, Yongxian; Chen, Yin; Zhang, Jianfeng; Pinhu, Liao (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) can lead to acute respiratory distress syndrome (ARDS) and life-threatening multi-organ failure with increased levels of inflammatory mediators and viral load; however, little is known about its pathophysiology. Methods: To better understand the cellular status of COVID-19-induced ARDS, we performed single-cell RNA sequencing on peripheral blood samples from patients with COVID-19-induced ARDS. Single-cell RNA sequencing combined with bioinformatics analysis was used to study dynamic changes in cell composition and transcriptional profiles. Results: The single-cell RNA sequencing data revealed significant phenotypic differences between patients with COVID-19-induced ARDS and controls, mainly in monocytes, and CD8+ T and B cells. B cell and monocyte abundances were significant in COVID-19-induced ARDS patients compared to controls, while CD8+ T cells were depleted. These data suggest that there is an imbalance between lymphocytes and monocytes in the blood of COVID-19-induced ARDS patients. In addition, cytokine interactions between T cells, monocytes and B cells are enhanced as evidenced by the intercellular communication analysis. In particular, T cell subsets target receptors on other cells via CCL5 and may play an important role in patients with COVID-19-induced ARDS. Conclusions: Our analysis suggested that a dysregulated adaptive immune response exists in patients with COVID-19-induced ARDS. Overall, we provided a cellular picture of the peripheral immune response in patients with COVID-19-induced ARDS.